Rational Expectations and Financial Ratio Smoothing - WU, Chunchi (Institutional Knowledge at Singapore Management University, 1994)
The article presents a study of rational expectations and financial ratio smoothing. Dynamic adjustment models have been used in traditional accounting and financial analysis to capture the temporal pattern of financial ratios. Empirical studies of financial ratio adjustment based on these models typically use the current or past industry average ratio as the desired target. The determination of the correct desired target ratio is important for analyzing financial ratio adjustment. The issue of expectation formation is relevant for the type of financial ratio adjustment model considered here involving an adjustment lag. When there is no adjustment lag, expectations are generally irrelevant because a firm can always respond to any change in the market conditions. The paper proposes a rational expectations-partial adjustment model to explain the behavior of some important financial ratios. The model incorporates a process of expectation formation, which is considerably more general than any of the previous specifications in the financial ratio movements rather well.